American Lightships, 1820-1983 : History, Construction, and Archaeology within the Maritime Cultural Landscape - MacKenzie, Morgan (East Carolina University, 2011)
In 1820, the United States Government began funding construction and conversion of watercraft for use as lightships. Floating beacons utilized to mark dangerous shoals, reefs, and shifting channels in inland as well as open waters, lightships served where lighthouse construction was unfeasible. This study intends to examine the general history of U.S. lightships, improvements to construction design, technological modifications in illumination and signaling, venue of employment, as well as use, re-use, and the maritime cultural landscape associated with these craft.
Keywords: Archaeology; Naval engineering; Military history; Lightships; Maritime cultural landscape; Navigational aids; Swiftsure; United States. Coast Guard; Lightships--United States--History; Shipbuilding--United States--History; Marine engineering--United States; Naval architecture--United States; Military archaeology--United States